Feasibility of Ultrasound in Infant Wrist and Thumb Imaging. (20th October 2018) - Milks, Kathryn; Warren, Patrick; Popp, James; Samora, Julie Balch
Abstract : Objectives: To determine the feasibility of ultrasound (US) in infant lateral carpal and base‐of‐the‐thumb imaging. We hypothesized that US would be a practical modality for visualizing the unossified structures. Methods: Institutional review board approval was obtained for this single‐center pilot study. Healthy infants aged 12 months or younger were enrolled. Ultrasound examinations of the distal radial epiphysis through the first metacarpal were performed with a high‐frequency transducer. Results: Ultrasound evaluations of the base of the thumb were performed in 18 healthy infants (mean age ± SD, 13.8 ± 9.1 weeks; 44% female). Assuming an elliptical shape, the mean areas of the scaphoid and first metacarpal epiphysis measured 0.85 ± 0.19 and 0.44 ± 0.087 cm 2, respectively. The mean areas of the trapezium and ossified first metacarpal as approximate rectangular shapes measured 0.23 ± 0.069 and 0.49 ± 0.16 cm 2 . A perimeter tracing was also used as an alternative area calculation. The mean trapezium area–to–scaphoid area ratio (0.28 ± 0.10) showed less variability compared to the first metacarpal epiphysis area–to–scaphoid area ratio (0.55 ± 0.20) or first metacarpal area–to–scaphoid area ratio (0.64 ± 0.31). Conclusions: Our data suggest that US is well suited for the evaluation of the lateral carpus and base of the thumb in young infants. These data serve as a reference to which wrist and thumb abnormalities can be compared.